Regional insights on the prevalence and antimicrobial susceptibility pattern of carbapenem and colistin-resistant gram-negative bacteria: an observational cross-sectional study from Karachi, Pakistan - Nazia Khursheed; Fareeha Adnan; Moiz Ahmed Khan; Ramlla Hatif (BMC Infectious Diseases)
Abstract Background Colistin is used to treat multidrug-resistant gram-negative bacteria. Rising colistin resistance worldwide has created challenges in effective treatment and raised treatment costs. Our study aimed to understand the prevalence of colistin resistance in carbapenem-resistant gram-negative bacteria, associated pathogens and their antimicrobial susceptibility pattern at our institute, to help limit further development of resistance. Methods An observational, cross-sectional study was conducted at the Microbiology laboratory of Indus Hospital & Health Network, Karachi, Pakistan from January 1, 2022 to December 31, 2023. Variables extracted from the electronic patient care database included the type of patient samples, clinical diagnoses, frequency of carbapenem-resistant gram-negative bacteria and antimicrobial susceptibility profiles. Microsoft Excel software (Microsoft Excel 2013 {15.0.5553.1000} 32-bit) was used for analysis. Susceptibility results were interpreted in accordance with the M100 guidelines of the Clinical and Laboratory Standards Institute. Results A total of 1,785 carbapenem-resistant gram-negative bacteria were isolated during the study period. Thirty (1.7%) of these exhibited colistin minimum inhibitory concentrations of ≥ 4 µg/ml and were characterized as colistin-resistant. Most patients with colistin-resistant gram-negative bacterial infections were males (57%), aged 31–49 and ≥ 50 years (37% each), and in-patients (60%). Majority had urinary tract infection (34%), followed by bloodstream infection (30%), ventilator-associated pneumonia (23%), and skin and soft tissue infection (13%). Organisms included Klebsiella species (77%), Acinetobacter baumanii (20%) and Pseudomonas aeruginosa (3%). Tigecycline was the most susceptible antibiotic among isolates (96%) while, fosfomycin (53%), minocycline (50%), doxycycline (45%) and tetracycline (42%) exhibited moderate susceptibility. Conclusion Our study highlights a concerning prevalence of colistin resistance (1.7%) among carbapenem-resistant gram-negative bacteria, particularly Klebsiella species, predominantly affecting male in-patients aged 31–49 and ≥ 50 years. This significant therapeutic challenge is underscored by the limited efficacy of available antibiotics, with only tigecycline showing high susceptibility (96%) and others like fosfomycin (53%) and minocycline (50%) offering moderate alternatives.